Self-Determination and Cultural Diversity - Glennon, Michael (Tufts Archival Research Center, 2005)
Volume 27, Issue 2. Summer/Fall How does a ï¿½rightï¿½ to self-determination fare next to the state practice of intervention? If self-determination leads to cultural homogeneity, does it also lead to oppression?